Toxicity of insecticides against (Optatus palmaris Pascoe) in soursop - Hernández-Fuentes, Luis Martín; Nolasco Gonzalez, Yolanda; Santos, Mario Orozco; Montalvo Gonzalez, Efigenia (Revista Mexicana de Ciencias Agrícolas, 2021)
Originally from tropical America, the soursop (Annona muricata) has great potential and production expectations in Mexico. However, it presents pest problems that limit its cultivation. One of these is the fruit weevil (Optatus palmaris), whose damage detracts from quality and yield. Insecticides and repellants were evaluated: spinosad, spinoteram, azadirachtin, lambda-cyhalothrin, chlorpyrifos, imidacloprid and etofenprox. The percentage of mortality, fruit consumption was evaluated and the CL50 and TL50 were determined. One hour after application, 89.2% and 85.7% (α< 0.05) mortality were observed with lambda-cyhalothrin and chlorpyrifos at a concentration of 0.025 g ai L-1 and 2.4 g ai L-1, respectively. Spinosad and azadirachtin had no mortality effect at concentrations of 0.6 g ai L-1 and 32 g ai L-1, respectively (α< 0.05). At 12 h after the application spinosad (0.6 g ai L-1), lambda-cyhalothrin (0.0012 g ai L-1) and chlorpyrifos (0.24 g ai L-1) exerted more than 95% mortality (α< 0.05). Fruit consumption was lower with the application of lambda-cyhalothrin, 24.9% of consumed fruit (α< 0.05). The insecticide with the highest toxicity was imidacloprid with an CL50 of 0.06 g ai L-1 and TL50 of 0.3 h, followed by spinoteram with an CL50 of 0.96 g ai L-1 and a TL50 of 0.36 h. Azadirachtin did not cause mortality or decrease fruit consumption compared to the absolute control at concentrations of 0.32, 3.2 and 32 g ai L-1 (α< 0.05) therefore the use of this product is not recommended for the control of O. palmaris.
Keywords: anonaceae; borer; control